A Racist Little Hat: The MSG Debate and American Culture - Germain, Thomas (Columbia Undergraduate Research Journal, 2015)
Stop for a moment and ask yourself what you know about monosodium glutamate. If you’re anything like most Americans, your thoughts on the subject are probably simple: MSG is an artificial flavoring most often used with Chinese food, which should be avoided because it’s bad for you and gives you headaches. If this is your thinking, you’re not alone. For the past fifty years, this has been the conventional American understanding of MSG. But times change. Recently, a vocal movement has sprung up that advocates for an end to the stigma surrounding MSG, as detailed in a Buzzfeed article by John Mahoney titled, “The Notorious MSG’s Unlikely Formula For Success.” Mahoney suggests that a new cultural context is emerging, spearheaded by a group of celebrity chefs who take the iconoclastic position that we should reintroduce MSG to our palates. They argue that beyond the merits of its delicious savory flavor, referred to as “umami,” society’s trepidations about the ingredient are based on research born out of stark racism and bad science which have perpetuated a myth about MSG’s toxicity [1]. But the old guard isn’t going quietly, and just as vocal as the pro-MSG camp are those who fear a change to the status quo.